Spillover effects of minimum wages in a two-sector search model - Christoph Moser; Nikolai Stähler (Deutsche Bundesbank, 2009)
Labor market studies on the effects of minimum wages are typically confined to the sector or worker group directly affected. We present a two-sector search model in which one sector is more productive than the other one and thus, pays higher wages. In such a framework, setting a minimum wage in the unproductive sector to reduce the wage gap causes a negative spillover effect on the productive sector. While the effect on job creation in the (targeted) unproductive sector is ambiguous, job creation in the (non-targeted) productive sector unambiguously decreases. This is driven by the fact that a minimum wage increases the outside option of unemployed workers - contributing to wage determination in the productive sector. Welfare effects are ambiguous. In principle, we cannot exclude that a minimum wage in a two-sector search model is welfare enhancing due to the possibility of an above optimal level of productive employment since firms do not take into account the effects of their individual job creation on aggregated search costs.
Keywords: E24; J31; J64; J60; 330; minimum wages; matching models; two sectors; unemployment; welfare; Mindestlohn; Wirtschaftspolitische Wirkungsanalyse; Mehr-Sektoren-Modell; Arbeitsuche; Arbeitsproduktivität; Matching; Wohlfahrtseffekt; Theorie